2023
DOI: 10.3389/fchem.2023.1045697
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of early renal damage in asymptomatic hyperuricemia patients based on urine Raman spectroscopy and bioinformatics analysis

Abstract: Objective: The issue of when to start treatment in patients with hyperuricemia (HUA) without gout and chronic kidney disease (CKD) is both important and controversial. In this study, Raman spectroscopy (RS) was used to analyze urine samples, and key genes expressed differentially CKD were identified using bioinformatics. The biological functions and regulatory pathways of these key genes were preliminarily analyzed, and the relationship between them as well as the heterogeneity of the urine components of HUA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…It has been found that the levels of Thr, Trp, and Ala were increased in patients with HUA compared with healthy individuals [ 33 ], which were consistent with our findings. It is worth noting that abnormalities in tryptophan metabolism showed association with AHU [ 34 ] and acute gout [ 35 ]. The altered levels of Trp may be owing to the UA-induced dysfunction of multidrug resistance protein 4 (MRP4) and breast cancer resistance protein (BCRP) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the levels of Thr, Trp, and Ala were increased in patients with HUA compared with healthy individuals [ 33 ], which were consistent with our findings. It is worth noting that abnormalities in tryptophan metabolism showed association with AHU [ 34 ] and acute gout [ 35 ]. The altered levels of Trp may be owing to the UA-induced dysfunction of multidrug resistance protein 4 (MRP4) and breast cancer resistance protein (BCRP) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning is used in various elds of biology to analyze association patterns between traits and genes in samples [8,9] . Machine learning is a subset of AI that has presented notable bene ts in ltering disease biomarkers or underlying prevention and treatment targets, and has been successfully applied in multiple diseases [10,11] . High-throughput sequencing data deposited in the GEO database were employed for the screening of underlying biomarkers and molecular mechanisms of RA, which can offer novel perspectives in preventing and treating RA.…”
Section: Introductionmentioning
confidence: 99%